The Interpersonal Communication of Prophet Muhammad in Dialogic Hadiths - Munawir Munawir; Musta'in Musta'in (Postgraduate Program, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Prophet Mohammed’s interpersonal communication is an appealing topic to study not only the way the communication is conveyed but also the effectiveness of the communication. Though his assignment as a messenger of God was relatively short, around 23 years, he was able to communicate his Islamic messages (teachings) to the Arab community successfully. He turned the Arabs from rejecting and confronting Islam into accepting and defending it. There are factors contributing to this success, and one of them is his interpersonal communication skill. This study attempts to describe Mohammed’s interpersonal communication through a deep investigation into dialogic prophetic traditions (hadith). This study employs a descriptive-inferential method and a subjective communicative approach. The theory used in this study is that of interpersonal communication. The findings reveal five qualities supporting the effectiveness of Mohammad’s interpersonal communication in his dialogic hadiths. They are openness, empathy, supportive attitudes, positive attitudes, and equality.